2023
DOI: 10.1101/2023.03.01.530696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Effects of Cocaine and Morphine on the Diurnal Regulation of the Mouse Nucleus Accumbens Proteome

Abstract: Substance use disorders (SUDs) are associated with disruptions in sleep and circadian rhythms that persist during abstinence and may contribute to relapse risk. Repeated use of substances such as psychostimulants and opioids may lead to significant alterations in molecular rhythms in the nucleus accumbens (NAc), a brain region central to reward and motivation. Previous studies have identified rhythm alterations in the transcriptome of the NAc and other brain regions following the administration of psychostimul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…A recent proteomic analysis in the NAc after cocaine self-administration revealed sex-specific variations, underscoring cocaine's capacity to reconfigure proteomic profiles and modulate reward-associated behaviors (33). Another study focusing on diurnal rhythms in the mouse NAc found that cocaine administration precipitated alterations in proteins linked to glucocorticoid signaling and metabolism (34). However, the full spectrum of proteomic alterations triggered by cocaine in the NAc, as well as their precise contributions to CUD pathophysiology, awaits further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent proteomic analysis in the NAc after cocaine self-administration revealed sex-specific variations, underscoring cocaine's capacity to reconfigure proteomic profiles and modulate reward-associated behaviors (33). Another study focusing on diurnal rhythms in the mouse NAc found that cocaine administration precipitated alterations in proteins linked to glucocorticoid signaling and metabolism (34). However, the full spectrum of proteomic alterations triggered by cocaine in the NAc, as well as their precise contributions to CUD pathophysiology, awaits further elucidation.…”
Section: Introductionmentioning
confidence: 99%